Strategi Pemasaran Digital untuk Meningkatkan Loyalitas Pelanggan di Era Media Sosial - Muhammad Iqbal (Universitas 45 Surabaya, 2025)
This study examines digital marketing strategies implemented by businesses in the creative industry and their relationship with customer loyalty. The crucial issue raised was how businesses can leverage social media to increase customer engagement and loyalty in the midst of fierce competition. The problem faced is a lack of understanding of the effectiveness of digital marketing strategies in building long-term relationships with customers. The purpose of this study is to explore and analyze the strategies used and their impact on customer loyalty. The research method used is observation and interviews with business people who are active on social media. The results of the study show that consistent interactions and relevant content contribute significantly to customer loyalty. The conclusion of this study emphasizes the importance of implementing the right digital marketing strategy to support business sustainability in a sustainable e-commerce ecosystem